Hubungan antara Kebiasaan Membaca dengan Keterampilan Berpikir Kritis Peserta Didik Di Sekolah Dasar - Nurul Fadilla; Puri Pramudiani (Jurnal Elementaria Edukasia, 2023)
The purpose of this study was to determine the relationship between reading habits and critical thinking skills of students in elementary school.  The practice of reading has an impact on the increase of one's knowledge and also on the ability to think critically.This study used quantitative research with the correlational analysis method. The research targets are 50 students in SDN Batu Ampar 09 East Jakarta grade 3. The study was conducted from November 2022 to July 2023 in the even semester of the 2022/2023 school year.  In this study, non probability sampling techniques with saturated sampling techniques were used. The results of this study showed the value of r count is 0.618 while r table is 0.288 at the 5% significance level. Therefore, the null hypothesis (h0) is rejected, while the research hypothesis (h1) is accepted, meaning that there is a positive who have level interpretations moderate or sufficient correlation between reading habits and critical thinking skills The results of this study can be used as a reference for the development of learning strategies in primary schools.